Clinical uses of Bupropion in patients with Parkinson’s disease and comorbid depressive or neuropsychiatric symptoms: a scoping review - Matteo Vismara; Beatrice Benatti; Gregorio Nicolini; Ilaria Cova; Edoardo Monfrini; Alessio Di Fonzo; Vincenza Fetoni; Caterina A. Viganò; Alberto Priori; Bernardo Dell’Osso (BMC Neurology, 2022)
Abstract Objective Bupropion, an antidepressant inhibiting the reuptake of dopamine and noradrenaline, should be useful to treat depressive symptoms in patients with Parkinson’s disease (PD). Limited and conflicting literature data questioned its effectiveness and safety in depressed PD patients and extended its use to other neuropsychiatric symptoms associated with this disorder. Design The databases PubMed, Embase, Web of Sciences, Cochrane Library, and the grey literature were searched. Following a scoping review methodology, articles focusing on Bupropion uses in PD patients who manifested depressive or other neuropsychiatric alterations were reviewed. Results Twenty-three articles were selected, including 7 original articles, 3 systematic reviews or meta-analyses, 11 case reports, 1 clinical guideline, and 1 expert opinion. Bupropion showed considerable effectiveness in reducing depressive symptoms, particularly in relation to apathy. Solitary findings showed a restorative effect on compulsive behaviour secondary to treatment with dopamine as well as on anxiety symptoms. The effect on motor symptoms remains controversial. The safety profile of this medication seems positive, but additional precautions should be used in subjects with psychotic symptoms. Conclusion The available literature lacks good evidence to support the use of Bupropion in PD patients presenting depressive symptoms. Further investigations are needed to extend and confirm reported findings and to produce accurate clinical guidelines.